Time-varying monetary-policy rules and financial stress: Does financial instability matter for monetary policy? - Baxa, Jaromír; Horváth, Roman; Vašíček, Bořek (Journal of Financial Stability, 2013)
We examine whether and how selected central banks responded to episodes of financial stress over the last three decades. We employ a recently developed monetary-policy rule estimation methodology which allows for time-varying response coefficients and corrects for endogeneity. This flexible framework applied to the USA, the UK, Australia, Canada, and Sweden, together with a new financial stress dataset developed by the International Monetary Fund, not only allows testing of whether central banks responded to financial stress, but also detects the periods and types of stress that were the most worrying for monetary authorities and quantifies the intensity of the policy response. Our findings suggest that central banks often change policy rates, mainly decreasing them in the face of high financial stress. However, the size of the policy response varies substantially over time as well as across countries, with the 2008–2009 financial crisis being the period of the most severe and generalized response. With regard to the specific components of financial stress, most central banks seemed to respond to stock-market stress and bank stress, while exchange-rate stress is found to drive the reaction of central banks only in more open economies.